(i) The functional equation of exp:
(ii) exp(-x)=1/exp(x)\exp(-x)=1/\exp(x) for all x∈ℝ.x\in{\mathbb{R}}.
(iii) exp(p/q)=ep/q\exp(p/q)=e^{p/q} for any integers pp and qq with q≠0q\neq 0.
(iv) expx>0\exp x>0 for all real xx.
(v) expx→∞\exp x\rightarrow\infty as x→∞x\rightarrow\infty; whereas expu→0\exp u\rightarrow 0 as u→-∞u\rightarrow-\infty.
Proofs (i) One needs to multiply the series together.
(ii) exp0=1+0+…=1;\exp 0=1+0+\dots=1; by (i), we also have exp(x)exp(-x)=exp0=1\exp(x)\exp(-x)=\exp 0=1, so exp(x)≠0\exp(x)\neq 0 and exp(-x)=1/exp(x).\exp(-x)=1/\exp(x).